KECEPATAN PROSES CETAK MOTOR DC MESIN OUTDOOR TERHADAP KEPUASAN KONSUMEN PADA PT. SEMBURAT LENTERA SEMESTA - Idris Shuhada; Desmira Desmira (Jurnal Universal Technic, 2022)
Outdoor Digital Printing Machine is a printing machine or digital printing machine whose printouts are intended for outdoors and are weather-resistant, both hot, sunlight and rain. Outdoor machines use a special type of ink, namely solvent ink. The principle of the outdoor machine itself is to print the design results that were previously in the computer. To drive an outdoor machine requires expertise and understanding in its use and there is a mode of acceleration of the printing process on an outdoor machine whose acceleration of the printing process is not yet known, where the acceleration of the printing process can affect consumer satisfaction. This study aims to 1) Knowing about Digital Print Tools as well as. 2) Knowing the use of Outdoor Digital Printing Machines. 3) Knowing the print speed of the outdoor machine. 4) Knowing the percentage of customer satisfaction. The research method used is the R&D method. By using the R&D method, the results obtained to determine the speed of the outdoor engine on the printhead motor with LOW mode have a speed of 124 m/s, MIDELL mode has a speed of 161 m/s, while HIIGH mode has a speed of 241 m/s. s. The results obtained to determine consumer satisfaction with the speed of the print rate through the time of using the machine using the Guttman scale, namely the overall process time of the outdoor digital printing printing machine on customer satisfaction has a conformity, which is indicated by the percentage of answers "Yes" an average of 75%.